GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG BANTUAN HIDUP DASAR (BHD) DI WILAYAH KERJA UPTD PUSKESMAS JATILUHUR PURWAKARTA - Dina Hartini; Wirdan Fauzi Rahman; Reyan Budi (Bajang Institute, 2024)
Emergency events include situations where the victim stops breathing and stops the heart. Another worst situation is if you experience an accident and require immediate assistance, for example bleeding. It is true that certain things do not immediately claim an individual's life, but if they occur if they are not treated immediately, they can cause the victim to suffer disability or even death. The aim of this research is to determine the level of community knowledge about Basic Life Support (BHD) in the Jatiluhur Purwakarta Community Health Center UPTD Work Area. This research uses a quantitative type of research with a descriptive research design, and uses a purposive sampling technique to collect sample data that is adjusted to the predetermined inclusion criteria, namely 1). Respondents are people in; 2). Respondents were willing to fill out the questionnaire and become research respondents, which consisted of 123 samples. The results of the research show that the level of insight of residents of Jatiluhur Purwakarta Community Health Center UPTD Work Area regarding basic life support is generally good with results (66.7%) The level of knowledge of respondents based on age, there are 33 respondents (26.8%) in the early adult category with good knowledge and 1 respondent (0.8%) final adult category with less knowledge; The level of knowledge of respondents based on gender, there were 47 respondents (32.2%) women with good knowledge and 1 respondent (0.8%) woman with poor knowledge; Respondents' knowledge based on education level, there were 42 respondents (34.1%) with a high school/vocational school education with good knowledge and 1 respondent (0.8%) with a D3 education with poor knowledge. Through this research, the author concluded that the level of knowledge of respondents based on age was 33 respondents (26.8%) in the early adult category with good knowledge; The level of knowledge of respondents based on gender, there were 47 respondents (32.2%) women with good knowledge; Respondents' knowledge based on education level, there were 42 respondents (34.1%) with high school/vocational school education with good knowledge